THE RELATIONSHIP BETWEEN ESR, HEMATOCRIT, PLATELETS COUNT AND OUTCOME OF CNS TUMOR PATIENTS WHO RECEIVED CHEMOTHERAPY AT RSUP DR. KARIADI SEMARANG - Budi, Hyasinta Paramita; Rahmawati, Maria Belladona; Budisulistyo, Trianggoro; Muhartomo, Hexanto (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background : Central nervous system tumors, both primary and secondary tumor, are malignancies which result in mental disorder, and neurological deficit. Therefore, the patients can end up being social burden for their environment. Hematological laboratory test including ESR, hematocrit, and platelets count are very practical. However, they are functional for predicting outcome. Aim: The current study aimed to determine the relationship between ESR, hematocrit, platelets count, and outcome of CNS tumor patients who received chemotherapy at RSUP dr. Kariadi Semarang. Method : This recent study was conducted at Medical Record Installation by collecting data from patient’s medical record. Data taken by researcher were hematologic profile (ESR, hematocrit, and platelets count), demographic data (age, gender, type of tumor, symptomatic treatment, and comorbidity), and outcome. Data were analyzed using univariate analytical method to show data distribution, bivariate analytical method to determine the relationship with outcome, and multivariate analytical method to determine which variable had the most significant relation. Result : Bivariate analytical method using chi-square test showed insignificant p value for hematocrit (p=0,541 total data, p=0,960 case, p=0,518 control). Platelets count analysis didn’t give significant p value either (p=0,541 total, p=0,790 case, p=0,292 control). There were no data could be obtained about ESR. Conclusion : The current study showed no relationship between hematocrit and outcome, neither the relationship between platelets count and outcome.Keywords : ESR, hematocrit, platelets count, outcome